THE EFFECT OF CASH FLOW, ACCOUNTING PROFIT, TOTAL ASSET TURN OVER ON MANUFACTURING COMPANY STOCK RETURN ON THE INDONESIA STOCK EXCHANGE - Yumina Telaumbanua; Dianty Putri Purba; Yunita Sari Rioni (Jurnal Ekonomi, 2023)
The research carried out has the aim of conducting an analysis of the influence that exists in cash flow, profit on accounting and total assets turn over on manufacturing company stock returns on the IDX. The data used in the research is secondary data which comes from a number of financial reports on the IDX. The sampling method used is purposive sampling and the data processing method used is multiple linear regression method, T-test and F-test through SPSS 20 software. The results show that operating cash flow has a large impact on stock returns partially, and accounting profit has a large impact. on stock returns partially. Meanwhile, operating cash flow, accounting profit, and Total Asset Turn Over simultaneously have a major impact on stock returns.